Kartini in two lenses: The shifting image of Indonesian modern woman in R.A. Kartini (1982) and Kartini (2017) - Chusna, Aidatul; Utami, Shofi Mahmudah Budi; Subuhi, Moh. Imam (Informasi, 2024)
This paper aims to examine the construction of Kartini figure in two Indonesian films titled R.A. Kartini (1982) and Kartini (2017) and how it represents the idealization of Indonesian woman in both eras. By utilizing textual analysis, the study finds different images of Kartini presented in the films. The 1982 film tends to emphasize on the critical nature of Kartini and her anti-colonial attitude. Moreover, Kartini is also presented as a figure of Javanese woman who is characterized by her feminine gestures and manner. Meanwhile, the 2017 film constructs Kartini figure differently. Instead of focusing on her femininity, the film constructs Kartini as an energetic, and rebellious young woman. The different characterizations of Kartini presented in the films indicate the shifting image of an idealized woman in both eras. As the first film produced in 1982, the ideal woman is represented as a feminine and motherly figure. Meanwhile in the second film, Kartini is imagined as the representation of the female millennial generation, characterized by their productivity, and creativity.